2019
DOI: 10.33012/2019.16699
|View full text |Cite
|
Sign up to set email alerts
|

Increasing International Civil Aviation Resilience: A Proposal for Nomenclature, Categorization and Treatment of New Interference Threats

Abstract: Electromagnetic interference can degrade civil Global Navigation Satellite System (GNSS) signals and services, and in some cases result in integrity failures. The aviation community is well-aware of such threats due to the proliferation of interfering-capable equipment including personal electronic devices (PEDs), personal privacy devices (PPDs), GNSS repeaters, mis-operated test equipment, low-cost software-defined radio cards, and the foreseeable proliferation of more sophisticated spoofing devices in the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…The future of SatNav on-board of aircraft is expected to follow some evolutionary trends that also will open new research challenges and will shape future research directions [2], [12], [260]- [263]. The main trend in GNSS is certainly the development towards dual/multi-frequency and multi-constellation receivers in order to improve accuracy, availability, continuity, and resilience to atmospheric effects, multipath and interference.…”
Section: Challenges Future Trends In Navigation For Aircraft Andmentioning
confidence: 99%
“…The future of SatNav on-board of aircraft is expected to follow some evolutionary trends that also will open new research challenges and will shape future research directions [2], [12], [260]- [263]. The main trend in GNSS is certainly the development towards dual/multi-frequency and multi-constellation receivers in order to improve accuracy, availability, continuity, and resilience to atmospheric effects, multipath and interference.…”
Section: Challenges Future Trends In Navigation For Aircraft Andmentioning
confidence: 99%
“…Interrupting the GPS signal can lead to DoS, errors in PVT measurements or reporting of falsified location and time information by the receiver. Irrespective of the intention of the emitter, any GPS interference signal can be considered as a variant of either jamming or spoofing, as also categorized by Fernandez-Hernandez et al (2019) . Jamming leads to DoS that may affect continuum and availability of guidance signals; whereas, spoofing may result in violations in data integrity if the malicious signal is considered as valid by the receiver.…”
Section: Gps Threat Landscapementioning
confidence: 99%
“…The authors concluded that the military GPS signal shows robustness against the jamming signal, while the civil GPS signal is more susceptible to jamming. Further detailed discussion of jamming and related RF interference affecting the GPS signal have been explored by Fernandez-Hernandez et al (2019) and Gerdan, Coombe & Takac (1995) . In particular, Fernandez-Hernandez et al (2019) categorized the GPS jamming threats into four types based on objectivity of exposure and sophistication of attack; whereas, Gerdan, Coombe & Takac (1995) presented three different case studies of the adverse effects of jamming on GPS signal’s acquisition.…”
Section: Gps Threat Landscapementioning
confidence: 99%
“…As next, the second user starts to move northwards with the speed of 5 km/h. This type of spoofing attack can be classified as "S7 -Targeted Sophisticated Spoofer" according to the nomenclature proposed by U.S.-EU Working Group C in [7]. Such spoofers can potentially use multiple phase-synchronized transmit stations in order to overcome the receiver defense strategies based on multiple receiving antennas and exploitation of the spatial properties of incoming signals.…”
Section: Spoofing Scenariomentioning
confidence: 99%